A framework for effective implementation of lean production in Small and Medium-sized Enterprises - Amine Belhadi; Fatima Ezzahra Touriki; Said El Fezazi (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: The present paper aims at developing an effective framework including all the components necessary for implementing lean production properly in Small and Medium-sized Enterprises. Design/methodology/approach: The paper begins with the review of the main existing framework of lean implementation in order to highlight shortcomings in the literature through a lack of suitable framework for small companies. To overcome this literature gap, data of successful initiatives of lean implementation were collected based on a multiple case study approach. These initiatives has been juxtaposed in order to develop a new, practical and effective framework that includes all the components (process, tools, success factors) that are necessary to implement lean in Small and Medium-sized Enterprises. Findings: The proposed framework presents many significant contributions: First, it provides an overcoming for the limitations of the existing frameworks by proposing for consultants, researchers and organizations an effective framework for lean implementation in SMEs that allows SMEs to benefit from competitive advantages gained by lean. Second, it brings together a set of the more essential and critical elements of lean implementation commonly used by SMEs and derived from the practical experiences of them in lean implementation. Finally, it highlights the successful experiences of small companies in implementing lean programs and then proves that lean can give a relevant results even for SMEs. Research limitations/implications: The proposed framework presents a number of limitations and still evokes extension for further researches: Although it was derived from practical experiences of SMEs, the proposed framework is not supported by practical implementation. On the other hand and even though the elements in the proposed framework from the practical experiences of four SMEs, the identified elements need to be generalized and enriching by conducting a survey to identify more elements that are also commonly used in SMEs. Practical implications: Implementing rigorously the proposed framework will help small companies' managers to improve considerably their organization's performance and benefits from lean strategies outcomes. Researches and practitioners in small businesses now possess an integral framework for successfully implementing lean strategies. Originality/value: To the best knowledge of the authors, this is the first work that proposes an effective lean implementation framework believed to be easy to understund, practical and suitable for small companies. In short, this study is a real quantum leap to resolve the problematic unanswered of lean implementation in SMEs.
Keywords: 650; lean production; framework; implementation; small to medium sized enterprises